STUDI KONSUMSI BAHAN BAKAR SOLAR PADA MESIN INDUK KM. FORTUNA - Boby Wisely Ziliwu (Machine : Jurnal Teknik Mesin, 2022)
Consumption of fuel oil (BBM) at a fishing port is usually much influenced by the number of ships and what types of fishing vessels are actively operating in the fishing port. The more the number of fishing vessels operating, the more the amount of fuel oil (BBM) needed and vice versa. Basically the number of fishing vessels operating depends on the fishing season. The type of fishing vessel also affects the characteristics of fishing vessels, such as trip time and fishing ground area. The role of diesel fuel is very important for capture fisheries activities, especially to support the operation of each ship with purse seine fishing gear available at PT. Batam True Sea Products. One of them is KM. Fortuna. The making of this report aims to calculate the amount of solar demand that exists on KM. Fortuna. Field research was conducted for approximately 25 days. Primary data were collected through observations and interviews with 1 engine room head (KKM) and 1 crew member in the engine section of the KM. Fortuna Secondary data obtained directly from PT. True Sea Products. Diesel fuel for the needs of purse seine ships in the port usually depends on the size, type, and length of time the ship operates at sea, for KM vessels. Fortuna was given a supply of diesel fuel per sail of 12,941,181 liters or 11 tons.